Coping Mechanism and Its Related Factors among Diabetes Mellitus Patients - Muflihah, Ulfatul; Asriyadi, Fitroh; Wahyuni, Khusnul; Alfiani, Lili; Sulvina, Sulvina; Syifa, Reza Nabilla; Puspitasari, Intan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes Mellitus (DM) is a disease that is increasing in number every year in both developed and developing countries . Diabetes mellitus is a disease that cannot be cured, so you have to undergo various types of treatment throughout your life. Coping mechanisms are ways used by sufferers to adapt to stress, solve problems, adjust to changes that have occurred, and respond to something that threatens them. the sufferer Chronic diseases require adaptive coping mechanisms for the healing process. Objective: to analyze factors related to coping mechanisms in diabetes mellitus patients. Method: a descriptive correlational research design with a cross-sectional approach was used. The sample size was 96 respondents. The sampling technique used was purposive sampling. Data was collected by filling out questionnaires by diabetes mellitus patients who met the inclusion criteria. The data analysis used was Multivariate Analysis with Binary Logistic Regression. Results: Only family support has a relationship with coping mechanism with a significance value of 0.004 < 0.05, with a strength of relationship of 0.265. Conclusions: The conclusion of this study is that of several factors related to coping mechanisms in diabetes mellitus patients, it was found that only family support had a relationship.